Interface, instructional approach, and domain learning with a mathematics problem-solving environment - Yadrick, Robert M.; Wesley Regian, J.; Robertson-Schule, Linda; Gomez, Catherine Connolly (Computers in human behavior, 1996)
In this paper, we conceptualize computer-based instruction (CBI) as involving both a primary task, learning a particular domain, and several secondary tasks centered around learning to use the instructional approach and manipulate the interface efficiently. We argue that the complexity and compatibility of the domain, instructional approach, and system interface separately and interactively influence the ease with which students are able to learn the subject matter. Examples show how looking at CBI in this way provides a framework for better understanding the results of some previous studies of CBI and CBI-related interface design. We also describe an experiment that attempted to dissociate the separate effects of these components on domain learning. The experiment examined the pretest-posttest performance differences of remedial subjects who learned to solve mathematics word problems.